House prices and the macroeconomy in Europe: Results from a structural var analysis - Matteo Iacoviello (European Central Bank (ECB), 2000)
A structural vector autoregressive (SVAR) approach is used to identify the forces driving house prices fluctuations in France, Germany, Italy, Spain, Sweden and the UK over the period 1970-1998. Quarterly time series for real house prices, GDP, money, inflation and interest rates are characterised by a multivariate process driven by supply, nominal, monetary, inflationary and demand shocks. It is found that: (1) tight money leads to a concomitant fall in house prices and GDP; (2) the house price responses to a monetary shock can be partly justified by the different housing and financial market institutions across countries; (3) monetary and demand shocks drive most of the short-run house price volatility. The paper also interprets the main house price cycles and their links with the real economy in light of the estimates shocks.
Keywords: C32; E32; E52; R21; 330